2021
DOI: 10.3389/fpls.2021.729560
|View full text |Cite
|
Sign up to set email alerts
|

Blocking miR530 Improves Rice Resistance, Yield, and Maturity

Abstract: MicroRNAs fine-tune plant growth and resistance against multiple biotic and abiotic stresses. The trade-off between biomass and resistance can penalize crop yield. In this study, we have shown that rice miR530 regulates blast disease resistance, yield, and growth period. While the overexpression of miR530 results in compromised blast disease resistance, reduced grain yield, and late maturity, blocking miR530 using a target mimic (MIM530) leads to enhanced resistance, increased grain yield, and early maturity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 47 publications
(57 reference statements)
0
12
0
Order By: Relevance
“…We then selected miRNAs that are known to participate in stress response regulation in potato, based on the data from [ 66 ]. For example, binding sites for miR530 (MSTRG.15777.2), a known regulator of immune responses in plants [ 68 ] were found on 3 DE-lncRNAs. Two of these transcripts were upregulated under single heat stress ( Table S9 ).…”
Section: Resultsmentioning
confidence: 99%
“…We then selected miRNAs that are known to participate in stress response regulation in potato, based on the data from [ 66 ]. For example, binding sites for miR530 (MSTRG.15777.2), a known regulator of immune responses in plants [ 68 ] were found on 3 DE-lncRNAs. Two of these transcripts were upregulated under single heat stress ( Table S9 ).…”
Section: Resultsmentioning
confidence: 99%
“…We also found that some miRNAs have a significantly different accumulation in both cultivars, these include miR397‐3p, miR530, miR7122, miR170, and miR403. These miRNAs, which were more abundant in Desiree compared with Eva, have been found to be involved in plant responses to stress (Dong & Pei, 2014 ; Kohli et al, 2014 ; Li et al, 2021 ; Manacorda et al, 2021 ; Xia et al, 2013 ). Future research efforts would determine whether these miRNAs are responsible for some of the stress responsive differences between Desiree and Eva.…”
Section: Discussionmentioning
confidence: 99%
“…Perturbation of Osa-miR530 enhances resistance to blast disease through its effects on H 2 O 2 accumulation. It is important to mention that blocking the Osa-miR530 also positively affects flowering and seed maturation [ 36 ]. The Osa-miR439a negatively affects immunity by inhibiting the expression of defense-related genes and H 2 O 2 production Suppression of the Osa-miR439a using target mimic mutants has been shown to compromise susceptibility to M. oryzae by induction of H 2 O 2 [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…General observations indicate that miRNAs enhance the immunity to pathogens and herbivores with significant positive effects on yield maintenance in most cases. For example, the Osa-miR159, Osa-miR162, Osa-miR396 , Osa-miR530 , Osa-miR1432, and Osa-1871 have been shown to have positive effects on yield component traits even when the plant is challenged by pathogens [ 24 , 26 , 32 , 36 38 ]. For instance, the miRNA, Osa-miR156, fine-tunes resistance without significant penalty to yield, while Osa-miR1873 confers resistance with only a minor penalty to yield [ 23 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation